From Educational Failure to Social Success - G. E. Zborovsky; P. A. Abramova (Moscow Polytechnic University, 2019)
The article presents an analysis of educational failure of Russian students, as well as the resources needed to solve it. The urgency of the problem is revealed. Methodological approaches to its sociological research are substantiated. Among them - the theory of human capital, the resource approach, the theory of social community. The results of the authors' researches of higher education conducted in 2011-2017 have provided the empirical base of the study. The article gives an interpretation of the concepts of "educational failure" and "problem students" and dwells on the social causes of the phenomenon of educational failure. The authors argue that educational failure can be traced from school to college and University and then - to labour market. An unsuccessful student with a high probability will be an unsuccessful worker. The authors present a typology of modern students based on two criteria - the level of educational motivation formation and the readiness to study at University. Special attention is paid to the risks arising from the growing number of unsuccessful students in higher education institutions of provincial Russia. The article shows the prospects for overcoming educational failure of students.